Exploring the complex immunomodulatory effects and gut defense via oral administration of Astragali radix water extract to normal mice - Mi-Gi Lee; Youngju Song; Hee Kang (BMC, 2024)
Abstract Background Astragali radix (AR) is one of the most widely used traditional Chinese herbal medicines. It exhibits diverse biological activities, including immunomodulatory and anti-inflammatory properties; however, some of its activities have only been demonstrated in vitro. Objective To examine the effects of orally administered AR extract on immune cells and the intestine under physiological conditions, which bridges the gap between previously observed in vitro outcomes and in vivo results. Methods AR extract was prepared by hot water extraction. Three separate animal experiments were conducted to isolate macrophages, splenocytes, and the small intestine epithelium. For the macrophage preparation experiment, an intraperitoneal injection of sterile thioglycolate was administered. The mice received oral AR extract at doses of 0.1, 0.5, or 2.5 g/kg for ten days. At the end of each experiment, cells or tissues were isolated. A portion of macrophages and splenocytes were analyzed for the phenotypic changes. The remaining cells were cultured and stimulated with lipopolysaccharide (LPS) or mitogen ex vivo to assess activation status, proliferation, and cytokine production. Samples of the intestine were subjected to real-time RT-PCR. Results Peritoneal macrophages from AR-treated mice exhibited increased expression of scavenger receptors, including SRA and CD36. Stimulation of these macrophages ex vivo with LPS selectively modulated the inflammatory response, including reduced expression of the costimulatory molecules CD40 and CD86, which are important for T cell responses, without affecting TNF-α and IL-6 production. Splenocytes from AR-treated mice exhibited a dose-dependent increase in CD4 and CD8 T cells; however, stimulation with mitogen decreased T cell proliferation and reduced IFN-γ production, which is essential for macrophage activation. An analysis of the small intestinal epithelium revealed an attenuated antimicrobial response, including reduced IgA content in the lumen and decreased expression of mucin-2 and polymeric Ig receptor genes. Conclusion The response of immune cells following oral treatment with AR extract did not replicate the previously documented in vitro findings. Immune cells and intestinal epithelium from mice administered oral AR extract exhibited a selective anti-inflammatory phenotype. The overall findings indicate that the systemic effects after oral administration of AR extract include reduced sensitivity to inflammatory insults.